Requisitos profesionales contemporáneos y educación en Enfermería: llamado a la reflexión (Avances en Enfermería, 2020)
Nursing professionals are part of the human resources in health in the world, playing a fundamental role in meeting the health needs of populations and in achieving the Sustainable Development Goals by nations. In this perspective, nursing knowledge, skills and values make their contribution unique and indispensable for the improvement of global health conditions, contributing to gender equality and strengthening economies [Fragmento de texto]